PERKEMBANGAN KONSEP PEMASARAN: IMPLEMENTASI DAN IMPLIKASINYA - Lukitaningsih, Ambar (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2014)
The development of the original understanding of marketing is more focused on the issue of physical distribution business enterprise then develop to the transaction which although not involve spending money and marketing activities also can be done by institutions outside the business. As a consequence of the expansion of the notion of marketing, the scope of marketing is also increasingly widespread. The process thus continues to bring more and more marketing phenomenon. But reality shows that although many businesses are aware of the importance of customer satisfaction, but still few of them are running customer service program is good and right. Program satisfying the customer is still limited and largely ceremonial slogan. They are more likely to hunt for new customers and ignore existing customers. This phenomenon can be seen in the allocation of marketing costs are largely devoted to the promotion and only a small portion devoted to retaining customers. Keywords: Marketing Concepts, Implementation, Implications.